PENGARUH PENAMBAHAN PROBIOTIK TERHADAP PANJANG DAN BOBOT OVIDUCT PADA AYAM NIAGA PETELUR AFKIR - Pratama, Danny; Mugiyono, Sigit; Sulistyawan, Ibnu Hari (ANGON: Journal of Animal Science and Technology, 2020)
Background. The purpose of this study is to look at its effects on lenght and weight of oviducts. Materials and Methods. The research method used was experimental with a completely randomized design (CRD) with treatment P0 (basal feed plus probiotic 0 ml / kg of feed), P1 (basal feed plus probiotic 1 ml / kg of feed) and P2 (basal feed plus probiotic 2 ml / kg of feed) and repeated 6 times and involved 72 chickens. Results. The results showed that the addition of probiotics had no significant effect (P> 0.05) on oviduct length. The addition of probiotics does not increase the length of the oviduct, it is suspected that the dose of the addition of probiotics is not correct because the protein content is not according to the needs, the feed protein content is still low, namely between 15.81% - 16.71%, besides that the length of the oviduct is affected because the chicken has reached adulthood genitalia which causes the chicken oviduct to reach its maximum size, will peak at the time of puberty and increase during the period of production constantly. The addition of probiotics had no significant effect (P> 0.05) on the weight of the oviduct. This is presumably because the nutrient content of the feed is not perfectly absorbed by the digestive duct, and laying hens that have been rejected have experienced a lot of fat or remnants of secretions formation of an egg in the oviduct channel thereby affecting the oviduct weights. Conclusion. The conclusion of this study is that the addition of probiotics to laying hens commercial chickens has not been able to increase the length and weight of the oviduct. Based on the results of this study the authors suggest that research should be conducted using a higher.